Question and Answer Learning Method for Enhancing Learning Effectiveness in Archiving Education - Sirajuddin Saleh; Mundzir Mundzir; Muh. Nasrullah (Journal of Educational Development and Learning (JEDAL), 2026)
The question-and-answer learning method is a strategy in the world of education that aims to increase interaction between teachers and students and encourage a deeper understanding of the learning material. The implementation of this method in a vocational school environment is an important aspect in assessing the effectiveness of learning, especially in the subject of Archives. This study focuses on the effectiveness of the application of the question and answer learning method at SMKN 5 Pangkep and identifies supporting and inhibiting factors in its implementation. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the application of the question and answer learning method in the subject of Archives at SMKN 5 Pangkep is quite effective. Several indicators that influence this effectiveness are: (1) interesting and challenging material, which is able to increase student involvement in the learning process; (2) varied questions, designed with various levels of difficulty to encourage students' critical and analytical thinking; (3) clear conclusions, which help students understand and connect the concepts that have been learned with practices in the world of work; and (4) good questioning techniques, using simple and easy-to-understand language so that students can respond more actively. However, this study also found challenges in implementing this method, such as a lack of confidence among some students in answering questions and the dominance of certain students in discussions. Some students tended to be passive due to fear of giving wrong answers or feeling less confident in actively participating in class discussions. This situation indicates that although the question-and-answer learning method has the potential to be successful in increasing learning effectiveness, additional strategies are needed to encourage equal engagement of all students. Therefore, a more inclusive approach and other supporting methods are needed to ensure that all students can be more actively involved in the learning process